The Ultimacy of the Penultimate: The Advaita Allegories of Niscaldas (1791–1863) - Barua, Ankur (Religions of South Asia, 2024)
The Sanskrit commentarial streams of Advaita Vedanta encompass a range of discursive styles such as systematized expositions of advaita, dialectical critiques of competing viewpoints, pedagogic outlines of spiritual disciplines, and so on. On this spectrum, the Yukti-prakas (‘The Light of Reasoning’) of Niscaldas (1791–1863) constitutes a distinctive style of presenting the viewpoints of Advaita through parabolic discourses which elaborate symbolic equivalences between characters in a narrative, on the one hand, and Vedantic concepts, on the other hand. We will explore seven of the many allegorical discourses sketched by Niscaldas in his attempts to re-orient the finite world as a pointer to the non-finite brahman. Niscaldas engages with a paradox that runs through many centuries of Advaita exegesis—namely, the use of human language to speak about the ultimate reality that ineffably transcends all conceptualization. The writings of Niscaldas are dynamic embodiments of translatory processes of vernacularization—the language is an early modern form of Hindi which is infused with local styles. Thus, Niscaldas is a highly significant mediating figure in the intellectual history of Vedanta—he has an immersive familiarity with the commentarial traditions originating from Samkara, and he is able to convey their technical contents through everyday language.